Fish and meat intake in relation to colorectal adenoma in asymptomatic Korean adults - Kim, Young Sun; Okekunle, Akinkunmi Paul; Yang, Sun Young; Song, Ji Hyun; Youn, Jiyoung; Kwon, Gabby Yoon Jeong; Lee, Jung Eun (Frontiers in Nutrition, 2024)
Introduction Colorectal adenomas are recognized as precursors to colorectal cancer through the adenoma-carcinoma sequence. Identifying modifiable dietary factors that may inhibit cancer progression is critical, but epidemiologic studies in Asian populations are scarce. Methods This study explored the impact of fish and meat intake on colorectal adenoma risk among Koreans. The study enrolled asymptomatic adults who visited Seoul National University Hospital Healthcare System Gangnam Center for health check-ups from May to December 2011. All participants underwent screening colonoscopy and completed a validated food frequency questionnaire. The study included 536 adenoma patients, 135 high-risk adenoma patients and 1,122 adenoma-free controls. Using multivariate logistic regression, we calculated odds ratios (ORs) and 95% confidence intervals (CIs) for fish and meat intake related to colorectal adenoma status, significant at p < 0.05. Results The intake of total fish, meat, red meat, chicken or processed meat showed no clear association with the prevalence of colorectal adenoma after adjusting for age, education, smoking status, alcohol intake, physical activity, body mass index, metabolic syndrome, colorectal cancer family history, total energy intake, and total fruit and vegetable intake. However, higher fish intake was associated with lower odds of high-risk colorectal adenoma, with a significant trend observed across quartiles (P for trend = 0.04). This trend was more pronounced among men than women (P for trend = 0.01). Conclusion In conclusion, we observed a significant inverse association between high fish intake and the prevalence of high-risk adenoma, but there were no clear associations between red and processed meat or chicken in the Korean population.